The power of sunspots: An experimental analysis - Dietmar Fehr; Frank Heinemann; Aniol Llorente-Saguer (Federal Reserve Bank of Boston, 2012)
The authors show how the influence of extrinsic random signals depends on the noise structure of these signals. They present an experiment on a coordination game in which extrinsic random signals may generate sunspot equilibria. They measure how these signals affect behavior. Sunspot equilibria emerge naturally if there are salient public signals. Highly correlated private signals may also cause sunspot-driven behavior, even though this is no equilibrium. The higher the correlation of signals and the more easily these can be aggregated, the more powerful these signals are in moving actions way from the risk-dominant equilibrium.
Keywords: C9; D5; 330; coordination games; strategic uncertainty; sunspot equilibria; irrelevant information